Fusarium spp. an emerging fungal threat to leatherback (Dermochelys coriacea) eggs and neonates - Kuschke, Samantha G.; Wyneken, Jeanette; Cray, Carolyn; Turla, Emily; Kinsella, Megan; Miller, Debra L. (Frontiers in Marine Science, 2023)
Introduction Fungal diseases are a rising health problem globally, in humans, nonhuman animals, and plants. Emerging fungal diseases have been associated with mass mortality events. A recent example of fungal disease pathogenicity is sea turtle egg fusariosis (STEF). The pathogenicity of STEF has been linked to fungi within the Fusarium solani species complex (FSSC). This complex is composed of over 45 phylogenetically identifiable species commonly found in the environment. Species within the FSSC lineage have been isolated from the nests of multiple sea turtle species and are linked to decreased hatching success in all 7 of the extant sea turtle species. Fungi within this lineage are also known to cause cutaneous and subcutaneous infections. These fungi are not only a threat to sea turtles but also to other animals, including humans, that use coastal waters and beaches inhabited by Fusarium spp. The presence of Fusarium spp., in the context of sea turtle health, has not been investigated on southeastern Florida beaches which are fundamentally important for at least three sea turtle species that nest there in large numbers. Methods We performed a retrospective assessment of necropsy reports from dead captive leatherback neonates from 2010 to 2022 to assess the most common microscopic diagnoses and the presence of skin lesions associated with mycotic dermatitis. Additionally, live captive leatherbacks and dead-in-nest samples from the 2022 hatching season were used to assess the presence and effect of mycotic dermatitis in Juno Beach and Boca Raton, Florida, USA. This was accomplished by observing gross lesions, fungal cultures, and blood values. Results The retrospective analysis of dead captive neonates revealed that the diagnosis of mycotic dermatitis on histopathology has significantly increased since 2010. The assessment of gross skin lesions associated with mycotic dermatitis in dead and live captive leatherback neonates also revealed a similar increase. Investigations in live captive leatherbacks revealed fungal cultures positive for Fusarium spp. and significant differences in blood values at emergence between healthy turtles and those that later developed mycotic dermatitis. Discussion Positive dead-in-nest culture results suggest that Fusarium spp. are likely present in leatherback sea turtle nests in Boca Raton and Juno Beach, Florida, USA. Additionally, the occurrence of mycotic dermatitis in dead and live captive leatherback neonates suggests that the presence of Fusarium spp. in the nest likely affects leatherback neonates even after emergence.